Measuring Stock Value: The Impact of Financial Ratios on a Company's Stock Price - Karima, Mutia; Ghazali, Muhammad (Research of Economics and Business, 2025)
This study aims to analyze the effects of the Debt-to-Equity Ratio (DER), Price-to-Book Value (PBV), Price-to-Earnings Ratio (PER), and Return on Assets (ROA) on stock prices. This study utilized a sample of food and beverage consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) for the period from 2019 to 2021. The sampling technique employed in this study was purposive sampling, involving 12 companies. The method employed in this study is quantitative and utilizes secondary data. The research model employs multiple linear regression, utilizing the SPSS version 25 application. The results of this study are partial, specifically that the DER, PBV, PER, and ROA variables do not have a significant effect on stock prices. Simultaneously, all variables namely, DER, PBV, PER, and ROA do not affect stock prices. This research is expected to focus not only on the company's profit but also on its ability to generate cash, as it is only an illustration of the company's short-term performance. In addition, investors also need to pay attention to the performance of the company's organizational governance tools, so that they can obtain better corporate action information to inform their investment decisions.